Wewnętrzne bariery tworzenia innowacji produktowych w placówkach gastronomicznych - Chrobocińska, Katarzyna; Sadowska-Cekała, Monika (Internal Barriers of Product Innovations Created in Gastronomy Posts, 2006)
The company's market position determines many factors among which more and more essential meaning have the technological potential, patents and innovativeness. In the article the authors concentrate on the analysis of innovative activity of gastronomy posts, as well as on the internal barriers of new products creating. On the basis of a questionnaire audits show that the most important obstacles in initiation of new products are insufficient financial supplies. The other internal obstacles are: the lack of information about market needs, the lack of time and the lack of support on the part of the management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 129-134